Synergistic enhancement of heavy metal tolerance and reduction by indigenous bacterial consortia of Pseudomonas putida and Pasteurella aerogenes - Karzan Qurbani; Hevy Wsw; Rahel Khdhr; Safin Hussein; Bahra Ibrahim; Avin Mahmood; Lanya Hama; Frishta Ibrahim; Omid Amiri (Scientific Reports)
Abstract Effective remediation is needed to reduce environmental and health threats from heavy metal contamination. This work examines the bioremediation capability of a new bacterial consortium from the polluted Tanjaro River: Pseudomonas putida pUoR_24 and Pasteurella aerogenes aUoR_24. Research will evaluate the consortium’s ability to reduce copper (Cu), zinc (Zn), and nickel (Ni) concentrations in different environments. The study used microbiological methods to investigate metal tolerance, reduction efficiency, and growth optimization at varied temperatures, salinities, and pH levels. Results demonstrate the consortium’s superior metal tolerance, with Minimum Inhibitory Concentrations (MICs) of 8 mM for Cu and 7 mM for Ni. Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES) showed outstanding metal reduction rates of 84.78% for Cu, 91.27% for Zn, and 88.22% for Ni, exceeding those of individual strains. Based on Scanning Electron Microscopy (SEM) and Energy Dispersive X-ray (EDX) analyses, Cu exhibited the highest weight percentage (3.7%), followed by Ni (0.5%), while Zn was undetectable, suggesting preferential sequestration of Cu and Ni by the consortium. The consortium also displayed robust growth across a wide range of temperatures (20–37°C), salinities (up to 4% NaCl), and pH levels (2–11). These findings show that microbial consortia can establish eco-friendly bioremediation solutions for heavy metal-contaminated settings.